(untitled) (Jurnal Keamanan Nasional, 2024)
Trilateral cooperation between Indonesia, Malaysia, and the Philippines in the Sulu Sea is the latest security architecture in Southeast Asia. This cooperation leads to increasingly intensive relations between the three countries in the field of maritime security. Relations became close because of the common security threats experienced by the three countries. These threats vary from threats of terrorism, smuggling, piracy and other transnational crimes. The three countries then formed a joint system to be able to deal with this threat, this situation is hereinafter referred to as cooperative security. This study then has the aim of identifying the cooperative security framework implemented by Indonesia, Malaysia, and the Philippines for maritime security in Sulu Waters. Based on the idea of cooperative security put forward by Richard Cohen there are four rings that are important elements, namely (1 ) individual security, (2) maintaining peace, (3) mutual protection, and (4) actively promoting stability. The four rings are then used to explain the pattern of relations in the context of cooperative security involving Indonesia, Malaysia, and the Philippines. This study uses a qualitative method, with a descriptive approach to explain the overall identification of cooperative security that occurs.